Efek Pemberian Beberapa Sumber Fosfat dan Mikoriza Vesikular Arbuskula pada Bibit Tanaman Jarak Pagar (Jatropha curcas L.) di Medium Gambut - Anis Tatik Maryani; Nelvia ' (Jurnal Sagu, 2009)
This research was conducted at experimental plot, Faculty of Agriculture Riua University from September 2007 to Januari 2008. This research aimed to know the influence of mycoriza application, type of phosphate, and interaction of both factor, and the best mycoriza dosage and phosphate type toward the growth of Jathropa curcas seed. This research was conducted by Completely Randomized Design (CRD) consisted of 2 factor with 3 replication. The first factor was mycoriza application, and second factor was the application of some phosphate sources. The result of Various investigation Analysis was tested by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The parameters observed were plant height, number of leaves, stem diameter, dry weight, root protrude ratio, and percentage of mycoriza. It may be concluded from the research that the interaction between natural phosphate of Huinan China with 10 g mycoriza/polybag improves the growth of Jathropa curcas seed.